KEBIJAKAN POLITIK LUAR NEGERI ARAB SAUDI TERHADAP KRISIS SYRIA (2011-2014) - Fadhly khsan; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is intended to analyze the Saudi Arabia foreign policy toward Syria Crisis. In March 2011,Student of a School in Syria had written anti-governent slogan on their School’s wall. Syrian Police arrested tand tortured them as punishment to the Student, this action cause Syria people movement to protest the government regime and ask for freedom and democratic transformation. In this case, Syria government tried to handle demonstration with the military action, This conflict increases faster and becomes armed conflict between opposition and Syria government. This research has built by using realist perspective of international relations and supported by foreign policy theory from Rossenau. This research also using nation-state as the level of analyze which aimed on Arab Saudi policy to Syira about the Syria Crisis. Formulation of facts, data, arguments, theoretical framework in this research using qualitative explanation methods. This research has formulated answer-hypothesis that Saudi Arabia doing massive foreign policy to press Syria when the crisis like propaganda, diplomatic action, support the opposition, and support military intervention to Syira is to pursue the main intersest which to reach hegemony position in middle east. Saudi Arabia has become major power in middle east, but Syria-Iran coalition is the main threat and obstacle for Saudi dominance. Saudi Arabia takes opportunity of Syria Crisis to increase its influence and power and also to make Syria as supporter to Arab Saudi in pursue hagemoni in the middleeast.Keywords: Syria Crisis, Saudi Arabia, Syria Regime, Foreign Policy, Hagemony, Security, Instability, National Interest.